New Trend of Islamic Education in Indonesia - Jamhari Jamhari (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
The concept of modern pesantren introduced by Imam Zarkasyi has become a blueprint and genre for the development of the next modern pesantren. Zarkasyi's students who are now spreading all over Archipelago establish a number of similar pesantren pioneered by the kyai. During the period of 1970-80s, a couple of Gontor alumni established pesantrens in their own region. In Banten, PesantrenDaar El-Qalam was established in Gintung Balaraja; in MaduraPesantren Al-Amin was established in Prenduan Sumenep in Central Java Pesantren Pabelan was established in Pabelan; Pesantren Modern Assalaam was established in Solo; and many others. Those pesantrens are frequently called pesantren alumni (meaning the alumni of Gontor), the second generation which have influenced the model of other modern pesantren in their later development.DOI: 10.15408/sdi.v16i2.482